Reducing Adolescent Anxiety Using a Spiritually Integrated Mobile Health Intervention: A Quasi-Experimental Study - Warih Puspitosari; Rizky Setyoningsih; Nusaibah Mar'atush Shalihah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Anxiety is a prevalent psychological issue among adolescents, which, if not properly managed, can negatively impact their mental well-being. This study aims to assess the impact of the Go-Soul application on adolescent anxiety levels, providing an alternative intervention that incorporates spirituality. Methods: A quasi-experimental study with a non-equivalent control group design was conducted. The study involved 50 participants from SMP Muhammadiyah Kasihan, Bantul Regency, Yogyakarta. Participants were assigned to either an intervention group using the Go-Soul application or a control group without intervention. The Taylor Manifest Anxiety Scale (T-MAS) was used to measure anxiety levels before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Pre-test results indicated that 68% of participants in the intervention group and 64% in the control group exhibited high anxiety levels. After the intervention, 56% of the intervention group displayed moderate anxiety, demonstrating a significant reduction (p = 0.014), whereas the control group showed no significant change (p = 0.564). Conclusion: The Go-Soul application effectively reduces adolescent anxiety levels. Spiritual interventions delivered through digital platforms can serve as a promising strategy to improve adolescent mental health. More broadly, the integration of culturally grounded elements—such as Qur’anic recitation in this context—demonstrates how digital mental health tools can be tailored to align with local values, beliefs, and practices. Such culturally sensitive approaches not only enhance user engagement and acceptability but also expand the relevance and impact of digital health innovations in diverse populations.